Cyberflashing recognising harms, reforming laws - McGlynn, Clare 1970-; Johnson, Kelly ca. 20./21. Jh (Bristol University Press, 2021)
Cyberflashing has been on the rise since the Covid-19 pandemic. This book provides new analysis into the harms of cyberflashing. This timely and unique study considers recent laws in several countries and sets out proposals to criminalise cyberflashing in English law
Title from publisher's bibliographic system (viewed on 05 Jan 2022)
Keywords: Indecent exposure / Law and legislation / England; Indecent exposure / Law and legislation / Wales; Computer crimes / Law and legislation / England; Computer crimes / Law and legislation / Wales